Implementation of the Childbirth Planning and Complication Prevention Program in Padang City - Nabila Alfina; Joserizal Serudji; Fika Tri Anggraini (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
The Planning and Complication Prevention program encourages pregnant women to have their pregnancies, deliveries, postpartum examinations and babies born by skilled health workers, including screening for complete tetanus immunization status in every pregnant woman. If the implementer has a positive attitude and support for implementing the P4K program, the P4K program may run according to the initial plan. The purpose of this study was related to the Implementation of the Childbirth Preparation and Complication Prevention (P4K) Program in Padang City. This research is a qualitative study with a phenomenological design. This research was conducted in the working area of Lubuk Kilangan Health Center, Lubuk Buaya Health Center and Pegambiran Health Center in January - May 2023. The informants in this study were 23 informants, namely five key informants, six main informants, and 12 additional informants. Data collection methods use in-depth interview methods, observation and document review-data validity by triangulating sources, methods and data. The research results obtained on the input component in each component have run well according to the requirements. Only the monitoring and evaluation component is not yet available in the process component. Moreover, the output component has been carried out well despite shortcomings because not all activities run optimally. Research suggestions are expected to increase family participation in implementing P4K, such as counselling and socialization, and increase discipline in following the recommendations of health workers assisted by Community Health Center cadres. Keywords: Component, Monitoring, Planning, Program